Urbanização desordenada e qualidade ambiental nas grandes metrópoles brasileiras: um estudo de caso sobre a perda da cobertura vegetal no Distrito Administrativo do Bengui (DABEN) em Belém/Pa) - COSTA, Suellen Cristina Vidal (2019)
The Brazilian cities grew horizontally to the peripheral areas in an accelerated and disorderly way, causing the loss of the vegetation of the same ones, as the process of periurbanization brought to the areas of urban expansion the construction of housing spaces and the consequent formation of new commercial centralities, Which in turn were replacing the vegetation cover evidenced a lack of urban planning that took into account the presence of vegetation as a vector of environmental quality in the space inserted. The Belém metropolis and its urban expansion areas fit into this reality, where the Bengui Administrative District (DABEN), currently has a great loss of vegetation cover, and what is still preserved, is isolated and dispersed in Public spaces and residential spaces, and with a degree of connectivity only within spaces belonging to the private initiative, making it impossible for the resident population to access the ecological and social benefits that vegetation can provide to them. DABEN's urban occupation history revealed that the construction of housing estates, the emergence of illegal settlements, the formation of residential condominiums, the verticalization process and the evident tertiarization of the economy brought significant vegetation loss, leaving only 11,06%, which is considered below the 30% recommended for an adequate adequate thermal balance in the space. Concomitant to this, a Vegetable Coverage Index per inhabitant (ICVH) of 13,07m² / hab, above 12m² / hab was diagnosed as the minimum to ratify environmental comfort in the space in which human beings coexist, but it is evident That the vegetation cover is distributed in a dispersed way, since the greater part of the population does not have direct access to the urban green. It is concluded that public policies that allow for the conservation of the vegetation of the private areas, construction and maintenance of the green areas, as well as the environmental awareness of the resident population, are necessary for the district study area, so that it can reconcile the Modernization of the urban space with the presence of vegetation cover, thus generating socioenvironmental benefits and consequently quality of life to the residents living there.